The Fabrication of a Gellan Gum-Based Hydrogel Loaded With Magnesium Ions for the Synergistic Promotion of Skin Wound Healing - Li, Wenqiang; Jian, Xingling; Zou, Yanfen; Wu, Lin; Huang, Haiyan; Li, Hui; Hu, Dandan; Yu, Bo (Frontiers in Bioengineering and Biotechnology, 2021)
In order to accelerate the serious skin burn wound healing in convenient manner, an interpenetrating network hydrogel consisting of gellan gum and polyacrylamide was synthesized by chemical crosslinking and Mg2+ ions immersion techniques. The prepared Mg2+@PAM/GG hydrogel was characterized by morphology, water vapour loss, swelling ratio, rheological properties, tensile mechanical, biocompatibility and flow cytometry study. The results showed that Mg2+@PAM/GG hydrogel mechanical strength could be enhanced by the dual network structure and physical crosslinking agent Mg2+ ions. In addition, the tension strength and of Mg2+@PAM/GG hydrogel is obviously increased from 86 to 392 KPa, the elongation at break increased from 84% to 231% and crosslinking density N increased from 4.3 to 7.2 mol/m3 compared to the pure GG hydrogel. The cumulative release curve of Mg2+ ions showed that the multiple release mechanism of Mg2+ ions and belong to non-Fick’s diffusion. Meanwhile, in vitro experiments show that Mg2+@PAM/GG double network hydrogel has favorable proliferation and NF-κB pathway inhibition property for fibroblast cells. Finally, the healing effect of the Mg2+@PAM/GG was evaluated in rat full-thickness burns model. The animal study demonstrates that Mg2+@PAM/GG could accelerate the healing efficiency in cause of the sustained-released Mg2+ ions into wound beds. Considering these excellent performance, this convenient prepared hydrogel has great potential commercial application for skin full-thickness burns healing materials.